The challenge of teaching undergraduates evidence‐based veterinary medicine. (16th September 2017) - Dean, R.; Brennan, M.; Baillie, S.; Brearley, J.; Cripps, P.; Eisler, M. C.; Ewers, R.; Handel, I.; Holmes, M.; Hudson, C.; Jones, P.; McLauchlan, G.; et al.
Abstract : The Royal College of Veterinary Surgeons now lists 'How to evaluate evidence' as a day one competence for newly qualified vets. In this article, representatives from each of the veterinary schools in the UK discuss how the challenge of delivering and assessing the concepts of evidence‐based veterinary medicine in a crowded undergraduate curriculum can be met.